Temporal and spatial variations in organic and elemental carbon concentrations in PM10/PM2.5 in the metropolitan area of Costa Rica, Central America - Herrera-Murillo, Jorge (2013)
PM2.5 and PM10 samples were collected at 4 and 14 sampling sites, respectively, located in the Metropolitan area of Costa Rica (MACR), during 2010-2011. These sites were representative of commercial, industrial and residential zones of this region. Concentrations of elemental carbon (EC) and organic carbon (OC) were analyzed using the IMPROVE thermal-optical reflectance (TOR) method. OC and EC concentrations were higher in commercial and industrial sites and showed clear seasonal variations with higher concentrations observed in the rainy season (May-November) than in the dry season (December-April), due to wind patterns in the study area. Total carbonaceous aerosol accounted for 35% of PM10 and 56% of PM2.5 mass. Good correlation between OC and EC in PM10 (R=0.89-0.75) and PM2.5 (R=0.79-0.64) indicated that they had common dominant sources of combustion such as industrial activities and traffic emissions. The annual average concentrations of estimated SOC (Secondary Organic Carbon) in the MACR PM10 samples showed values between 0.65-8.49 mg/m3, accounting for 48% and 56% of the OC in PM10 and PM2.5 respectively. Positive Matrix Factorization (PMF) identified five principal sources for OC and EC in particles: gasoline vehicles, diesel vehicles, on road traffic, wood smoke and industrial combustion. The contribution of each of the source varied between the PM10 and PM2.5 size fractions.